(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article is mainly about the ways through which we can improve the creative thinking of our young generation. In the process of modern education, the importance of higher education is considered important. Focusing on the strategies of any developed countries, we can see that the beginning of the achievements, undeniable intellectual opportunities are realized through the reform of the education system. The global processes, the need for an innovative society, the development of Science and technology, along with the creation of many opportunities for young people, put before them such pressing demands as rapid decision-making, the formation of innovative thinking, the development of intellectual potential.